An Analysis of Context of Culture and Context of Situation in Obama’s Speech Text - samsudin, samsudin (Lingual Journal of Language and Culture; Vol 10 No 2 (2020): Lingual: Journal of Language and CultureDO - 10.24843/LJLC.2020.v10.i02.p04, 2020)
Functional systemic linguistics studies the meaning of texts. In Understanding the meaning of the text, it needs the involvment of situation context and cultural context. The aim of this research is to analyze the speech text conveyed Barack Obama in terms of situation context and cultural context.  This research used descriptive qualitative approach as research design. Technique of data analysis uses the context situation and cultural context analysis  as formulated by Suzanne Eggins (2004) and Halliday and Hasan (1985). The result showed that situation context is determined in term of field, tenor, and mode. The field of the text is about description of the problems faced by American State and how to solve those problems. The tenor of this text describes that relation between Barak Obama and the audience is not equal. The mode of the text shows that text was conveyed orally and rewrited by the jurnalist in the form of written text. Then, the cutural context is determined in term of the word choice in making the meaning of the text. in addition, cultural context is also detemined by the genre and the purpose of  text. Thus is analitical text by purposing to give the new hope and the solution solution about crisis happening in America.